2014
DOI: 10.1016/j.sbspro.2014.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater, Climate Change and Sustainable Well Being of the Poor: Policy Options for South Asia, China and Africa

Abstract: High population pressure and the rapid pace of human activity including urbanization, industrialization and other economic activities have led to a dwindling supply of arable land per capita as well as water, especially ground water in underdeveloped countries. This has entailed considerable damage to the physical environment, including degradation and depletion of natural resources and unsustainable use of land and water resources. With the impact of climate change, the depletion of water resources will be fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Banerji et al (2012) find that, in contrast to earlier literature, the observed water trades result in efficient water allocation across farms. Acharyya (2012) suggests changes in the existing institutions of irrigation in India for generating efficiency and proper groundwater irrigation management. Ma et al (2016) propose an evaluation model for groundwater used for irrigation, which take into account the infrastructure price, resource price and environment price based on monetary values.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Banerji et al (2012) find that, in contrast to earlier literature, the observed water trades result in efficient water allocation across farms. Acharyya (2012) suggests changes in the existing institutions of irrigation in India for generating efficiency and proper groundwater irrigation management. Ma et al (2016) propose an evaluation model for groundwater used for irrigation, which take into account the infrastructure price, resource price and environment price based on monetary values.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Shah et al (2009), while writing about canal water irrigation in West Bengal, tell us that public irrigation systems like canals grossly underprice irrigation and are getting marginalized. Acharyya (2014) shows that many canals in West Bengal are drying up due to inadequate rainfall and rising temperatures in the summer as part of climate change.…”
Section: Monopoly Power In Groundwater Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, over the last fifty years, groundwater development has played a fundamental role in agricultural production in many parts of the developing world [3]. Dependence upon groundwater is specially important in areas such as Northern China, Eastern Europe, Northern India, the US Great Plains and the largest parts of the middle east countries [4]. In the recent decades, due to many different factors, including climate change effects towards be warming and lower precipitation, as well as some structural policies such as more intensive harvesting of groundwater for agriculture development, low price of irrigation water, inefficient water use, the level of groundwater has decreased in most areas of Iran [5].…”
Section: Introductionmentioning
confidence: 99%
“…They found that groundwater recharge has not changed significantly, whereas long-term groundwater abstraction leads to huge deficit of groundwater in this area. Acharyya (2014) mentioned that rising population as well as impacts of climate change may lead to depletion of groundwater resources and dwindling supply of water in South Asia, China and Africa. Zhang et al (2014) analyzed the effects of land use/land cover changes on the groundwater fluctuations.…”
Section: Introductionmentioning
confidence: 99%